Factors that Influence the Interruption of Tuberculosis Treatment in Imenti South Sub-County, Meru Kenya - Waithaka, Samuel; Kei, Robert; Mbugua, Gabriel (International Journal of Professional Practice, 2019)
Tuberculosis (TB), which is a highly infectious air-borne disease is a major health problem in the world. Kenya is 15th in TB prevalence among 22 high TB burden countries in the world. TB treatment interruption refers to missing of appointments therefore a patient will miss taking drugs. This increases disease morbidity, mortality and contributes significantly to the development of Drug Resistant TB which is expensive to treat. Data on factors influencing TB treatment interruption in Imenti South were unavailable. The study objectives were to determine the demographic, health services, cultural and patient factors that influence TB treatment interruption. A descriptive cross-sectional study was conducted. Data was obtained from 247 TB patients randomly selected from treatment registers and who had missed taking drugs during the treatment period. Ten key informant interviews were conducted on Health Care Workers working in TB clinics. A researcher-administered questionnaire was used to collect data from HCWs and TB treatment interrupters. Data Collected was cleaned, coded and keyed into Statistical Package for Social Sciences (SPSS). Chi-square test was applied to identify the relationship between variables. Results were presented using tables. Results showed that majority TB treatment interrupters were male (71.6%). The most frequent age group was 15-34 years (50.2%). There was no association between demographic factors and TB treatment interruption (p>0.05). The largest number (41.5%) interrupted treatment because they forgot appointment dates. A leading number of TB treatment interrupters are smokers (60.9%) and alcohol abusers (60.9%). Low education level, low income and unemployment influences interruption of treatment. The health system should pay particular attention to male TB patients and age group 15-34 years old through sustained health messages. Substance abuse should be addressed through rehabilitation and health education. Reminding patients about appointments through SMS is important. Research to establish why males interrupt treatment more is recommended